2017
DOI: 10.1177/0268355517712884
|View full text |Cite
|
Sign up to set email alerts
|

A prolonged antibiotic protocol to treat persistent Chlamydophila pneumoniae infection improves the extracranial venous circulation in multiple sclerosis

Abstract: Objective Chronic cerebrospinal venous insufficiency (CCSVI) is a condition associated with multiple sclerosis (MS). One mechanism that has been proposed is that the venous obstructions found in MS are due to a chronic persistent venulitis caused by the intra-cellular bacterial parasite, Chlamydophila pneumoniae (Cpn). The objective of the current study is to determine the effect of a combined antibiotic protocol (CAP) on the venous flow in MS patients as measured by a quantitative duplex ultrasound examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Since then, differences in venous hemodynamics between MS patients and controls were not only observed by supporters, but also by critics of this hypothesis . As a consequence, experimental treatment approaches based on controversial hypotheses were published, aiming to cure venous anomalies in MS, ranging from venous angioplasty to prolonged antibiotic treatment against Chlamydophila pneumoniae …”
Section: Fisher's Exact Test Regarding the Distribution Of Ccsvi Critmentioning
confidence: 99%
“…Since then, differences in venous hemodynamics between MS patients and controls were not only observed by supporters, but also by critics of this hypothesis . As a consequence, experimental treatment approaches based on controversial hypotheses were published, aiming to cure venous anomalies in MS, ranging from venous angioplasty to prolonged antibiotic treatment against Chlamydophila pneumoniae …”
Section: Fisher's Exact Test Regarding the Distribution Of Ccsvi Critmentioning
confidence: 99%
“…Unfortunately, recent multicenter randomized controlled trials have concluded that endovascular treatment does not improve the outcome of MS, and suggested that endovascular treatment for MS patients should be discouraged until appropriate highquality trials confirm safety and efficacy [153]. Another perspective on CCVSI was provided by Thibault et al, who proposed that chronic persistent venulitis caused by Chlamydophila pneumoniae, an obligate intracellular bacterium, may play a role in CCVSI and other vascular diseases; their non-randomized cohort study found that extracranial blood flow improved after treatment with a combined antibiotic protocol [154][155][156]. In summary, although some CNS disorders appear to be associated with IJV stenosis, causal relationships between these entities and IJV stenosis have not been firmly established.…”
Section: Ijv Stenosis and Cns Disordersmentioning
confidence: 99%
“…However, a subsequent study detected Cpn in 15 of the atheromatous lesions as well as in three of the normal tissues [57], further suggesting that Cpn infection might be an initial trigger of atherosclerotic development. Cpn infections have also been reported in adult patients with multiple sclerosis, namely in venous obstructions due to Cpn-associated chronic persistent venulitis [60]. An increased risk of Cpn-associated cardiovascular events in HIV-infected Australians have also been evaluated [61], however the role of chronic infections (such as Cpn) in immunosuppressed patients, with respect to the possible increase in vascular events noted in association with HIV infection, remains to be elucidated.…”
Section: Chlamydia Pneumoniae-an Elusive Human Cosmopolitan Pathogenmentioning
confidence: 99%